STRATEGI PENINGKATAN PENJUALAN AIR MINERAL (AIR GALON) PADA APARTEMENT GREEN PARK VIEW, DAAN MOGOT JAKARTA BARAT (STUDI KASUS PADA TIGA PENYALUR PENJUALAN AIR MINERAL) - Ferry Wattimury (Soso-Q : Jurnal Manajemen, 2020)
This study aims to determine the strategy to increase sales of mineral water (gallon water) in the Green Park View apartment of three types of brands that are favored by consumers, Aqua, Cleo, Vit. This research is a qualitative study using a SWOT analysis tool. The data collection method is conducting interviews and observations. Based on the results of the research, the strategy taken is to strengthen the salesman team, strengthen brand identity, door-to-door, and set extreme strategies by raising selling prices and providing leeway for some time in paying off his first order. Whatever the policies of these three suppliers will have an impact on increasing profits for the company. Keywords: Marketing strategy, marketing mix, SWOT, qualitative